Entrenamiento de fuerza en adultos mayores con osteoporosis. - Murillo Condor, Leonela Maribi (2025)
The study aimed to investigate the effects of strength training in older adults with osteoporosis by reviewing the available scientific literature. The research critically examines the benefits and risks associated with this intervention, comparing them with other treatment modalities or control groups. The research design was documentary and bibliographic, using scientific databases such as Medline, PEDro, and ScienceDirect to obtain peer-reviewed articles and clinical trials with an inductive and retrospective approach. Analysis of the 25 selected articles, corresponding to clinical trials conducted between 2019 and 2024, evidenced that strength training was highly effective in improving bone mineral density, muscle strength, and balance in older adults with osteoporosis. These benefits significantly reduced the risk of fractures, falls, and injuries, improved quality of life, and promoted healthier and more active aging. Among the main conclusions, it was highlighted that strength training slows bone deterioration, improves physical safety in daily activities, and promotes functional independence, self-esteem, and emotional well-being in this population. Consequently, the importance of incorporating this type of intervention in treatment plans for older adults with osteoporosis was emphasized.